2021
DOI: 10.57125/fed/2022.10.11.17
|View full text |Cite
|
Sign up to set email alerts
|

Future educator's digital learning assets: global challenges of our time

Abstract: The rapid development of digital tools for education, their use in the teaching process for different purposes leads to the need for teachers to create pedagogical digital assets. Digital pedagogical assets are forms, means of interaction, the use of digital tools by the teacher for self-educational and educational purposes. This study presents the results of a survey of teachers regarding the characteristics of teaching with digital resources, the problems encountered and the characteristics of the educationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 7 publications
0
9
0
3
Order By: Relevance
“…At the same time, the study by Gumenyuk et al (2021) demonstrates that the development of modern curricula that take into account the needs and interests of students, as well as the requirements of the labor market, is important to ensure relevant learning. On the other hand, many modern works emphasize that important aspects of the digitalization of vocational education are the use of technologies in assessment, which affect the increase of objectivity and speed of the learning process, effective monitoring of learning, and the development of digital skills of teachers (Kelly, 2021;Kovalchuk et al, 2022b;Wojciech et al, 2021). Therefore, an important direction for the further development of vocational education in Ukraine is to prepare teachers and educators for the successful use of digital technologies in the educational process and their implementation in pedagogical practice.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, the study by Gumenyuk et al (2021) demonstrates that the development of modern curricula that take into account the needs and interests of students, as well as the requirements of the labor market, is important to ensure relevant learning. On the other hand, many modern works emphasize that important aspects of the digitalization of vocational education are the use of technologies in assessment, which affect the increase of objectivity and speed of the learning process, effective monitoring of learning, and the development of digital skills of teachers (Kelly, 2021;Kovalchuk et al, 2022b;Wojciech et al, 2021). Therefore, an important direction for the further development of vocational education in Ukraine is to prepare teachers and educators for the successful use of digital technologies in the educational process and their implementation in pedagogical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Radianti et al (2020) identified the importance of digitalizing design education through the use of virtual reality in higher education. The positive and negative effects of using the latest technologies were investigated by Wojciech et al (2021). Wojciech et al (2021) also traced the necessary level of digital competence for teachers to be sufficient to work effectively with modern technologies in education.…”
Section: Describe Relevant Scholarshipmentioning
confidence: 99%
“…The positive and negative effects of using the latest technologies were investigated by Wojciech et al (2021). Wojciech et al (2021) also traced the necessary level of digital competence for teachers to be sufficient to work effectively with modern technologies in education. Separate studies include those of Jiang (2020), who, by comparing China's training system with that of other countries, identified the importance of forming an aesthetic environment for students.…”
Section: Describe Relevant Scholarshipmentioning
confidence: 99%
“…In the near future, education will be focused on digitalization and the spread of ICT in various forms, and robotization in the manufacturing sector will only increase (Wojciech et al, 2021). In particular, international online trade has become more active, which has led to an increase in demand for specialists in the economic and logistics sector.…”
Section: Globalization and The Challenges Of The Work Environment: Im...mentioning
confidence: 99%